Alopecia Areata and it’s Association with Thyroid Dysfunction - Rai, Anjan; Yadav, Rajeev; Karki, Sunita; Pradhan, Manish (Journal of Nobel Medical College, 2021)
Background: Out of many cause of non-scarring alopecia, alopecia areata is one the cause of non-scarring alopecia. Most study till now has shown autoimmunity to be pathogenesis of alopecia areata and has found to be frequently associated with abnormal thyroid function. The current study aims to early detection of thyroid dysfunction in AA patient and reduce morbidity related to thyroid disorder. Materials and Methods: This was a prospective observational study conducted over a period of 1 year from July 2018 to June 2019 in department of dermatology Nobel Medical College, Biratnagar. Any patient who presented with clinical features of alopecia areata were included in the study. Results: In our study, only 5 (7.1%) patients showed abnormal thyroid function tests, and other 65 (92.9%) had normal thyroid function. 3 patients (4.3%) had hypothyroidism and 2 patients (2.9%) had hyperthyroidism. In those presenting with thyroid dysfunction, 3 (10.3%) were females and 2 (4.9%) were males Mean age of onset of alopecia areata was 27.8 years. Conclusion: Our study did not show significant association of alopecia areata with thyroid dysfunction. However this study showed male preponderance in alopecia areata though thyroid dysfunction was seen more in female.